Oral health academics' conceptualisation of health promotion and perceived barriers and opportunities in dental practice: a qualitative study - Stacey Bracksley-O'Grady; Karen Anderson; Mohd Masood (BMC, 2021)
Abstract Background Oral diseases place a significant burden on individual and population health. These diseases are largely preventable; health promotion initiatives have been shown to decrease the disease rates. However, there is limited implementation of health promotion in dentistry, this could be due to a number of factors; the ethos and philosophy of dentistry is focused on a curative, individualised approach to oral diseases, confusion around health promotion as a concept. Oral health academics are well placed to implement health promotion, training of these professionals needs to include prevention, as training influences dental practice. However, there is a little understanding about how oral health academics (dental professionals who educate dental and oral health students) view health promotion. The aim of this exploratory study is to understand how oral health academics conceptualise health promotion and perceive the barriers and possible opportunities for health promotion implementation in dental practice. Methods Nominal group technique (NGT), a highly structured face-to-face meeting, was conducted with 24 oral health academics to explore how they conceptualize health promotion and the barriers and opportunities for health promotion in practice. An additional 4 questions were emailed to oral health educators after the NGT meeting to gather additional data, 6 oral health academics were involved. The data was analyzed using thematic analysis. Results Three board themes were identified: "Knowledge, ideas and concepts of health promotion", "Challenges to health promotion", "Opportunities for health promotion practice". The oral health academics in this study discussed health promotion in a holistic way, however, health education and behaviour change were mentioned more than other aspects of health promotion. The structure of dental practice specifically the curative approach that underpins dentistry and the lack of funding, and value placed on health promotion could act as a challenge to health promotion being implemented in practice. There has been a shift towards prevention in dentistry, however the participants acknowledge there needs to be a change in the curative culture of the profession. Collaboration with other health professionals and using a common risk factor approach were the identified opportunities for health promotion practice. Conclusions Oral health academics have a holistic understanding of health promotion, but still focus more on behavioural approaches which is common within dentistry. For a change to occur in health promotion practice a change in the structure, curative approach and funding model of dentistry is required. Collaboration with other health professionals is an opportunity to be capitalised on. Training of future dental professionals is the perfect place to start to implement the changes and opportunities for health promotion presented in this paper.